Diffractive Elements for Zero-Order Bessel Beam Generation With Application in the Terahertz Reflection Imaging - Liting Niu; Kejia Wang; Yongqiang Yang; Qiao Wu; Xi Ye; Zhengang Yang; Jinsong Liu; Hengyong Yu (IEEE Photonics Journal)
Novel diffractive elements are presented to produce zero-order Bessel beams in the terahertz (THz) band. First, diffractive elements are designed as phase plates to change the direction of the incident Gaussian beam. Then, they are fabricated by the emerging three-dimensional printing technology. Last, zero-order Bessel beams are generated by the diffractive elements at 0.3 THz. To verify the feasibility of this approach, the generated zero-order Bessel beams are monitored and compared with the ones generated by the axicons. The comparison confirms that the diffractive elements can produce Bessel beam effectively and efficiently. In addition, the diffractive elements are applied to introduce zero-order Bessel beam to a THz reflection imaging system. A resolution test phantom is imaged by the THz reflection imaging system with zero-order Bessel beam and a conventional THz reflection imaging system. The results indicate that the THz reflection imaging system with Bessel beam offers a significantly extended depth of field and high anti-interference capability.